Problematika Relasi Orang Tua dan Lembaga Pendidikan Islam di Era Digital (Studi Kasus di SD Islam Miftahul Huda) Keringan Nganjuk - Muniir, Muhammad Mishbahul; Sofiyullah, M. Yusuf; Adha, Asyrul Hanni (JoEMS (Journal of Education and Management Studies), 2026)
ABSTRACT Purpose: This study aims to analyze the problems and challenges in the relationship between parents and Islamic educational institutions amid the shift towards digital platform-based interactions (such as WhatsApp and e-learning systems), as well as to analyze its implications for students' character building. Methodology/approach: This research employs a descriptive qualitative approach using a reflective autoethnography model, conducted at SD Islam Miftahul Huda Keringan Nganjuk. The researcher was directly involved as both a teacher and a homeroom teacher. Data were collected through experiential reflection, in-depth interviews with teachers and parents, and school document analysis. Findings: The findings indicate that while digital communication is highly effective for delivering academic information, it is less effective in strengthening character building without active parental involvement at home. Parents' busy schedules, limited supervision, and a lack of role modeling are the primary challenges in shaping students' discipline and moral values. Practical implications: Schools and families need to implement concrete collaborative strategies to strengthen partnerships in monitoring student development. This can be achieved through initiatives such as the My Parent My Teacher (MPMT) program and the use of Daily Activity books. Originality/value: This research contributes to the study of Islamic basic education by utilizing a reflective autoethnographic perspective from an educator. It emphasizes the importance of integrating digital communication with value-based collaborative partnerships between families and schools to support holistic character education in the digital era.